Study on Energy Gap and Refractive Index Relations in Perovskite Solar Cell - Deepak Choudhary (International Journal of Engineering and Management Research, 2020)
Perovskite are materials having the precious stone design of strontium titanate at room temperature (SrTiO3) with an overall recipe for the oxide analogs of ABX3, where A is a cation, for the most part an uncommon earth-or salt sort component, B is a change metal cation, furthermore, X is an oxide or halide anion. Lately, there has been a developing interest among material researchers in the investigation of perovskite. This is on the grounds that perovskite show an assortment of capacities, for example, piezoelectric, pyroelectric, and ferroelectric, photovoltaic cells, LEDs, superconductivity, and topological covers. By and large, oxide perovskite display great dielectric properties, and halide perovskite show brilliant photonic properties. Since the disclosure of calcium titanium oxide, CaTiO3, by Gustav Rose in 1839, the examination on perovskite stayed torpid until the 21st Century. The principal paper on lead halide perovskite was distributed in 1892. The design of CsPbI3, cesium plumbo iodide, was examined in 1959. It is just in the last decade that perovskite have acquired reputation as materials for photovoltaic change. The paper "Organo metal Halide Perovskite as Visible-Light Sensitizers for Photovoltaic Cells" by Kojima and Miyasaka et al. has been the impetus for the dramatic development of research on perovskite sun oriented cells. Because of their inborn direct energy hole that coordinates the sun oriented range, halide perovskite keep on performing admirably as photonic materials.